Metal-support interaction boosted electrocatalysis of ultrasmall iridium nanoparticles supported on nitrogen doped graphene for highly efficient water electrolysis in acidic and alkaline media. (August 2019) - Wu, Xiuju; Feng, Bomin; Li, Wei; Niu, Yanli; Yu, Yanan; Lu, Shiyu; Zhong, Changyin; Liu, Pingying; Tian, Ziqi; Chen, Liang; Hu, Weihua; Li, Chang Ming
Abstract: Strong metal-support interaction has been explored as an efficient way in heterogeneous catalysis to modulate the electronic structure of active metal for enhanced catalytic activity. Herein we report ultrasmall iridium nanoparticles supported on nitrogen-doped graphene sheets (Ir@N-G-750) with boosted electrocatalytic activity and durability toward hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) for highly efficient water electrolysis. As-reported Ir@N-G-750 demonstrates excellent HER and OER activity superior to benchmarking Pt/C and RuO2 /IrO2 catalysts, respectively in both acidic and alkaline media; as a bifunctional electrocatalyst, it enables long-term 1.6 V-overall water splitting at 20 mA cm − 2 current density when loaded on planar glassy carbon electrode at a total Ir loading of 23 μg cm −2 . Detailed investigation unveils abundant Ir–N coordination in Ir@N-G-750, which enhances the electron density and modifies electronic structure of Ir nanoparticles to facilitate the electrochemical reactions. Density functional theory (DFT) calculation indicates that N dopants can stabilize the supported Ir clusters and improve their electrocatalytic activities. Graphical abstract: Ir@N-G-750 demonstrates superb HER and OER activity and durability, outperforming Pt/C and IrO2 catalysts, respectively either in acid or in alkaline.Image 1 Highlights: Ir@N-G-750 exhibits HER/OER activity superior to Pt/C and RuO2 /IrO2 in acidic and alkaline media. Ir@N-G-750 enables stable water electrolysis at 20 mA cm −1 at 1.6 V at low loading. There are abundant Ir–N coordination and enhanced electron density on Ir metal. DFT calculation rationalizes the improved electrocatalytic activity and durability.